The religion in social work - Simões, Pedro (2024)
Religion is a theme discussed by all the classic social scientists but relatively forgotten in brazilian social work. However, the religious issues do not cease to cross the professional practice. From this observation, the article recovers some data produced mainly by Simões (2005) and others, to highlight some of the following questions: the themes derived from the debate about religion were always present and still remain relevant in the international agenda of social work; the brazilian social workers are mostly religious (christians); they have, historically, more participation in voluntary religious activities than political ones; they establish links of meaning between their professional training and their religious training. Thus, the absence of an open and systematic debate about religious mediation in professional practice remains to leave their professionals still acting based on good sense and common sense.